(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Histomorphological features of lake frog’s (Rana ridibunda) skin, living in coastal zone of the Hrazdan river, differing by impurity high level of waters are studied. Some destructive and adaptive-compensatory changes of the animals’ skin living in zones with high level of impurity are described.